Analisis Pola Asuh Orang Tua Dalam Penanganan Anak ADHD: (Attention Deficit Hyperactivity Disorder) - Chairani Avrilly; Ati Kusmawati; Kisti Alda Nurdiani; Rahil Aqilah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Children with special needs are children who have physical, mental and social characteristics that are different from normal children. ADHD is a disorder in which you see symptoms of poor concentration, hyperactivity, and impulsivity, which can cause an imbalance in most life activities. Parents have control over many factors that can positively influence their child's symptoms. The role of parents in developing the character of children with ADHD (Attention Deficit Hyperactivity Disorder) aims to develop the character of children with ADHD in terms of the child's emotional and social aspects. Adjusting life as a parent who has a child with ADHD so that the child can grow and develop optimally according to his or her potential. The Role of Parenting Styles in Handling Hyperactive Children (ADHD) in SLB Pedagogia Surabaya. Research shows that the type of parenting given to children with special needs is carried out with a democratic parenting style, and balances the power of easy control in providing education to children in an appropriate way.